Sensitive Skin in the Genital Area - Farage, Miranda A. (Frontiers in Medicine, 2019)
When evaluating sensitive skin, it is common to focus on the face. However, it is becoming increasingly clear that individuals can have different perceptions about the degree of skin sensitivity at distinct anatomic sites. Structural variations in the skin of different body sites can contribute to differences in barrier function, which may contribute to differences in skin sensitivity. Potential triggering factors for skin sensitivity would be expected to vary by body site. For example, the face is exposed to all ambient environmental conditions in the course of daily life, and to several products (e.g., cosmetics for women) and practices (e.g., shaving for men) that may lead to adverse sensations associated with sensitive skin. In contrast, the skin of the genital area is protected from ambient environmental conditions. However, the genital area can be exposed to conditions of higher temperature, different habits and practices and moisture due to the semi-occlusive environment. For some individuals, additional challenges such as incontinence can provide triggering factors for skin sensitivity that effect only the genital area. This article reviews data on the perception of sensitive skin of the genital area, differences based on gender, age, racial differences, and the effects of incontinence on skin sensitivity. The effects of menopause are also considered with regards to sensitive skin perceptions and to emerging differences in biomolecular and physical measures of the urogenital skin.